Pengaruh Pelatihan SIMPEGNAS Terhadap Proses Percepatan Kenaikan Gaji Berkala Pada Badan Kepegawaian Pendidikan Dan Pelatihan Daerah Kabupaten Sorong - Untajana, Paulus; Kastanya, James; Andisanty; Kopong, Anthoneta; Souisa, Novita (Universitas Pendidikan Muhammadiyah Sorong, 2025)
Sorong Regency as the parent regency, the ability to use information technology is absolutely necessary for the State Civil Apparatus (ASN) in improving public services. Thus, the community will feel served and as a form of government present in the midst of the community to meet their various needs. This transformation of government services provides a new work culture, new business processes, new policies and new regulations that are oriented towards electronic-based government (e-government). The Sorong Regency Government has implemented a computerized system for managing KGB in mid-2023. The computerized system in question is known as the National Personnel Information System abbreviated as SIMPEGNAS. SIMPEGNAS is a general application for national sharing in the field of personnel. Thus, every PNS or ASN can access it through the MyASN application for various needs concerning their careers, especially for managing periodic salary increases. Thus, it will simplify and accelerate the process of managing periodic salary increases and various other things related to PNS careers. This research was conducted at the Regional Education and Training Personnel Agency of Sorong Regency. This research was conducted for two (2) months, namely in the third week of April 2024 to the second week of June 2024, the population in this study was 3,624 people. The number of samples (size of simple) was determined based on the calculation of the Slovin formula. Data analysis in this study used multiple linear regression analysis techniques. Based on the research that has been carried out, in general the training carried out by the Sorong Regency BKPPD is in the very high category, namely an average of 444.5, especially in the aspect of leadership policies to help achieve goals, with a total score of 467 which is at a very high value.